Dıstrıbutıon Of Cyclıc-Amp In Mechanıcally-Stressed Perıodontal Fıbroblast Cells - Hakan Gögen; Zeev Davıdovıtch (Turkish Journal of Orthodontics, 1997)

(untitled)
Adenosine 3′, 5′-monophosphate (cAMP) is an intracellular mediator of the effects of external signals on target cells. Using immunohistochemistry, it has been observed that orthodontic forces alter the cAMP content in several cell types in the cat periodontal ligament (PDL). The objective of this study was to determine the effects of orthodontic forces on the intracellular distribution of cAMP in PDL fibroblasts. Twelve, one year old cats were treated by 80 g tipping force to one maxillary canine for 1. 7 and 14 days. Maxillary horizontal sections (5 m) were stained for cAMP. Cellular staining intensity was measured as percent light transmitted by computer aided microphotometry using the MAPS program (Zeiss). Both the nuclei and the cytoplasm of the cells on the treated side stained darker with respect to the control side, except for the nuclei at 1 day. The cytoplasm stained darker than the nuclei on the treated side at all time intervals. These results indicate that mechanical force affects the cAMP content and its intracellular distribution in periodontal cells.